Pancasila Sebagai Solusi Problem Bangsa - Susilawati Susilawati (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
The current situation of the Indonesian state is very alarming. So many problems have befallen this nation in the form of a multidimensional crisis. Economic, political, cultural, social, security and security crises, education and others, which actually lead to moral crises. Morality holds the key to being very important in overcoming crises. If moral crisis is the upstream of all problems, then morality can also be overcome through crisis. Morality provides the basis, color as well as determining the direction of action of a nation. Morality can be divided into three, namely individual morality, social morality and mondial morality. Individual morality is more an awareness of good principles that are inward, embedded in human beings that will affect the way of thinking and acting. Factors that Cause the Nation's Problems are: 1) Poverty, 2) Corruption, 3) Weak Law Enforcement, 4). Low Quality of Education, 5) Poor Management of Natural Resources, 6) Rampant SARA Cases 7) Social Inequality, 8) Congestion, 9) Unemployment and 10) Many Areas That Are Not Carried Out. While solutions to overcome the nation's problems are: 1) Fair in sharing power, 2) Equitable distribution of income, 3) Equitable education, 4) Equitable distribution of knowledge and insights, 5) Equitable health, 6) Equitable occupation and 7) Equitable security. The strategy in implementing Pancasila to overcome the nation's problems is to understand Pancasila correctly. Correct understanding is to understand Pancasila based on precepts upon precepts in detail and comprehensively in a unified whole.